The Sea Alms Tradition in Rowo Village, Kebumen: Adaptation to Environmental Uncertainty through Actor-Network Theory - Mubarok, Kasirul; Mundayat, Aris Arif; Ramdhon, Akhmad (Austronesia Akademika, 2025)
The relationship between humans and the environment has become a central focus in both social and ecological research, particularly among communities reliant on natural resources. This study examines the Sedekah Laut (Sea Alms) tradition practiced in Rowo Village, Kebumen Regency, as a cultural adaptation mechanism to address environmental uncertainty. The primary objective is to understand how this ritual reflects the community’s response to unpredictable natural conditions. Employing a qualitative approach grounded in Actor-Network Theory (ANT), the research explores the interactions between human and non-human actors involved in the tradition, including the sea, ritual objects, community leaders, and local beliefs. Data were collected through field observations, in-depth interviews, and document analysis. Findings reveal that Sedekah Laut is not only a symbolic expression of gratitude and spiritual reverence toward the sea but also serves as a practical strategy to reinforce communal bonds and manage uncertainty in a changing environment. The sea is perceived as both a provider and a sacred entity, deserving of respect and offerings. Through collective participation in the ritual, the community cultivates a shared sense of resilience, interdependence, and social solidarity. In conclusion, the Sedekah Laut tradition illustrates how local knowledge and cultural practices can function as adaptive strategies in the face of environmental challenges, offering insights into the dynamic relationship between society and nature as conceptualized through Actor Network Theory.